2023
DOI: 10.1213/ane.0000000000006397
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate NIMA-Related Kinase 2-Dependent Epigenetic Pathways in Dorsal Root Ganglion Neurons Mediates Paclitaxel-Induced Neuropathic Pain

Abstract: BACKGROUND: The microtubule-stabilizing drug paclitaxel (PTX) is an important chemotherapeutic agent for cancer treatment and causes peripheral neuropathy as a common side effect that substantially impacts the functional status and quality of life of patients. The mechanistic role for NIMA-related kinase 2 (NEK2) in the progression of PTX-induced neuropathic pain has not been established. METHODS: Adult male Sprague-Dawley rats intraperitoneally receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…MLT profoundly impacts the epigenetic regulation of gene expression, suggesting its potential utility in combination therapy with epigenetic drugs, presenting a novel approach to anticancer treatment . Our prior research revealed that the chemotherapy drug PTX heightened a pNEK2-dependent epigenetic process within the DRG, contributing to the development of neuropathic pain, a major side effect of PTX . Specifically, pRSK2 initiated the expression of pNEK2, leading to a reduction in H3K27me3 levels by increasing the JMJD3 activity.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…MLT profoundly impacts the epigenetic regulation of gene expression, suggesting its potential utility in combination therapy with epigenetic drugs, presenting a novel approach to anticancer treatment . Our prior research revealed that the chemotherapy drug PTX heightened a pNEK2-dependent epigenetic process within the DRG, contributing to the development of neuropathic pain, a major side effect of PTX . Specifically, pRSK2 initiated the expression of pNEK2, leading to a reduction in H3K27me3 levels by increasing the JMJD3 activity.…”
Section: Discussionmentioning
confidence: 97%
“…22 Our prior research revealed that the chemotherapy drug PTX heightened a pNEK2-dependent epigenetic process within the DRG, contributing to the development of neuropathic pain, a major side effect of PTX. 15 Specifically, pRSK2 initiated the expression of pNEK2, leading to a reduction in H3K27me3 levels by increasing the JMJD3 activity. This cascade of events resulted in the upregulation of TRPV1 gene transcription within the DRGs, which is a critical factor in PTX-induced neuropathic pain.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Furthermore, our previous study demonstrated that 1 spinal PRMT family member is involved in neuropathic pain 6 and that the histone methylation regulation of nociceptive gene expression in DRG neurons plays a key role in PTX-induced neuropathic pain. 7 Thus, increased PRMT5 expression in the DRG may be involved in PTX-induced neuropathic pain.…”
mentioning
confidence: 99%